2020
DOI: 10.35308/jpt.v7i2.2397
|View full text |Cite
|
Sign up to set email alerts
|

Kelimpahan, Keanekaragaman Dan Biomassa Ikan Karang Pada Perairan Ujong Pancu, Kabupaten Aceh Besar

Abstract: Reef fish utilize coral reef ecosystems as a place to live, foraging, spawning and nurturing. This study aims to determine the abundance of species, diversity and biomass of reef fish found in the waters of Ujong Pancu, Aceh Besar district. This research was conducted in October 2017, there were 5 research location. Data was collected using the Underwater Visual Census (UVC) method. The result show that the highest abundance of reef fish was found in waters of Lhok Mata Ie with a value of 5311.71 Ind/ ha. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
1
0
3
Order By: Relevance
“…Therefore, the average biomass obtained was lower compared to that of Lake Sembuluh and Papudak, Central Kalimantan (461.8 kg/ha) (Kartamihardja et al 2017). The results also showed that the value was slightly higher compared to Ujung Pancu, Aceh Besar (Fazillah et al 2020), and Mentawai Islands waters (Suparno et al 2021), namely 46.27 kg/ha and 205.79 kg/ha, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, the average biomass obtained was lower compared to that of Lake Sembuluh and Papudak, Central Kalimantan (461.8 kg/ha) (Kartamihardja et al 2017). The results also showed that the value was slightly higher compared to Ujung Pancu, Aceh Besar (Fazillah et al 2020), and Mentawai Islands waters (Suparno et al 2021), namely 46.27 kg/ha and 205.79 kg/ha, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…Tingginya nilai biomassa pada stasiun Kumbung disebabkan karena tingginya kelimpahan individu ikan lamun terutama jenis Gerres limbatus dan tingginya persentase tutupan padang lamun serta minimnya aktivitas antropogenik pada area padang lamun. Rendahnya nilai biomassa ikan lamun pada stasiun Tanjung kerasak dan Tanjung Ru disebabkan karena rendahnya kelimpahan ikan lamun dan rendahnya persentase tutupan padang lamun serta tingginya aktivitas antropogenik seperti aktivitas penangkapan ikan dan adanya kegiatan penambangan di area padang lamun (Fazillah et al, 2020). Faktor yang mempengaruhi biomassa ikan seperti kelimpahan ikan, sumber makanan, kondisi substrat dasar sebagai penyedia refleksi langsung dari besarnya kesempatan yang diberikan oleh habitat lamun dan tingkat pemanfaatan ikan.…”
Section: Hasil Dan Pembahasanunclassified
“…Pada stasiun 1 secara keseluruhan jumlah kelimpahan ikan terumbu karang lebih rendah dibandingkan dengan statiun 4, akan tetapi pada family Pomacentridae dan family Labridae jumlah individu lebih tinggi dibandingkan dengan stasiun 1 sehingga menghasilkan biomassa yang tinggi. Biomassa ikan terumbu karang yang tinggi berkaitan dengan jumlah individu yang tinggi dan ukuran tubuh yang panjang (Fazillah et al, 2020; I. M. R. Putra et al, 2018;Ritonga et al, 2022).…”
Section: Jumlah Individu Ikan Familyunclassified